MoS2-Modified Curcumin Nanostructures: The Novel Theranostic Hybrid Having Potent Antibacterial and Antibiofilm Activities against Multidrug-Resistant Hypervirulent Klebsiella pneumoniae - Singh A.K.; Mishra H.; Firdaus Z.; Yadav S.; Aditi P.; Nandy N.; Sharma K.; Bose P.; Pandey A.K.; Chauhan B.S.; Neogi K.; Vikram K.; Srivastava A.; Kar A.G.; Prakash P. (My University, 2025)
The recent emergence of hypervirulent clinical variants of Klebsiella pneumoniae (hvKP) causing community-acquired, invasive, metastatic, life-threatening infections of lungs, pleura, prostate, bones, joints, kidneys, spleen, muscles, soft-tissues, skin, eyes, central nervous system (CNS) including extrahepatic abscesses, and primary bacteremia even in healthy individuals has posed stern challenges before the existing treatment modalities. There is therefore an urgent need to look for specific and effective therapeutic alternatives against the said bacterial infection or recurrence. A new type of MoS2-modified curcumin nanostructure has been developed and evaluated as a potential alternative for the treatment of multidrug-resistant isolates. The curcumin quantum particles have been fabricated with MoS2 via a seed-mediated hydrothermal method, and the resulting MoS2-modified curcumin nanostructures (MQCs) have been subsequently tested for their antibacterial and antibiofilm properties against hypervirulent multidrug-resistant Klebsiella pneumoniae isolates. In the present study, we found MQCs inhibiting the bacterial growth at a minimal concentration of 0.0156 μg/mL, while complete inhibition of bacterial growth was evinced at concentration 0.125 μg/mL. Besides, we also investigated their biocompatibility both in vitro and in vivo. MQCs were found to be nontoxic to the SiHa cells at a dose as high as 1024 μg/mL on the basis of the tested adhesion, spreading of the cells, and also on the various serological, biochemical, and histological investigations of the vital organs and blood of the Charles Foster Rat. These results suggest that MQCs have potent antimicrobial activities against hvKP and other drug resistant isolates and therefore may be used as broad spectrum antibacterial and antibiofilm agents. Copyright © 2019 American Chemical Society.